Necrotizing fasciitis in association with Ludwig's angina - A case report - A.M. Kavarodi (Elsevier, 2011)
A 28 year old male diabetic patient developed Ludwig's angina which subsequently evolved into cervicofacial necrotizing fasciitis. The differential characteristic of Ludwig's angina and cervicofacial necrotizing fasciitis, as it relates to this rare presentation is discussed. The clinical and radiological features, pathophysiology, diagnosis and the management that resulted in a successful outcome are presented. Keywords: Necrotizing fasciitis, Ludwig's angina